Pemberian Pendidikan Karakter Dengan Relevansi Pedagogi Dalam Film Animasi Upin Ipin - Virda Adinda Larasati; Cucun Sunaengih; Aah Ahmad Syahid (Jurnal Elementaria Edukasia, 2023)
This study discusses the values of character education with pedagogical relevance in the animated film Upin and Ipin. The animated film Upin and Ipin is a quality children's film because it conveys education in the form of character education and transfers pedagogical values ​​that can help develop children's character. This study aims to find out how the relevance of pedagogical values ​​and educational values ​​in the animated film Upin and Ipin for elementary school children so that the focus of this research is on the character values ​​of the animated film characters Upin and Ipin. This type of research is a qualitative descriptive research. The method used is a documentation method for data collection and a content analysis method for analyzing data. The results of the study show that the animated films Upin and Ipin have character education values ​​and are relevant to pedagogy, namely religion, tolerance, social care, hard work, friendship, and responsibility. This study gives meaning to animated films as an effective medium for conveying education and character values ​​to elementary school-age children.